Air-suspension coating of dairy powders : a micro-level process approach : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Technology at Massey University, Palmerston North, New Zealand - Werner, Stephen R. L. (Massey University, 2005)
Air-suspension particle coating is a process by which thin coatings are applied to powder particles. The coatings can be formulated to act as permeable barriers to increase powder shelf-life or to impart controlled release character. The ultimate objective of a coating operation is to produce individual particles, each with a well-controlled, even coating. This project was focused on the air-suspension coating of fine powders of ~100 µm in diameter for the dairy industry. Despite the widespread use of the technology in the pharmaceutical industry, its use in the food industry has been limited. Little is known about the fundamental mechanisms, and so published work to date is product and equipment specific and is statistical in the way the experimental design and analysis has been approached. This 'black box' approach is time consuming and costly. Better methods based on an understanding of the physical and chemical mechanisms are needed to deal with the numerous products and constantly changing formulations typical of the dairy industry. This thesis proposes a new approach to air-suspension particle coating research. The basis of this 'micro-level process approach', is to deconvolute the complex coating process into smaller manageable parts based on classical physical phenomena for which descriptions already exist. The thesis identifies and develops an understanding of the key micro-level processes controlling coated product quality and process performance. Four were selected for further study: drying, droplet impact and spreading, and stickiness which encompasses the two key micro-level processes of droplet impact and adherence and inter-particle agglomeration. They were studied separately to deconvolute the variable effects and interactions. Kinetic data were collected for the drying droplets containing maltodextrins, whey protein isolate and gum arabic. A mathematical model, based on 'ideal shrinkage' was developed to predict the drying kinetics of single droplets with particular interest in the development of the surface glass transition temperature. The model accurately predicted the kinetics until significant morphological changes occurred in the droplet. To better predict the kinetics late in the drying process, the droplet radius was set to be constant at a time based on the surface proximity to the surface glass transition temperature (critical X concept). This was done to arrest droplet shrinkage in line with experimental observations and to more accurately depict the drying of high molecular weight, amorphous glass forming polymers. After this point, a new flexible calculation scheme was used to better predict the variation in internal droplet structure as either a dense, 'collapsed shell' structure or a 'dense skin-porous crumb' structure. Further study should focus on the surface and internal droplet structure (porosity and mechanical integrity) development during drying, particularly the conditions leading to the arresting of the droplet radius and the subsequent rate of skin thickness progression. The critical X concept was used to make industrial-scale predictions of the optimum drying conditions that ensure maximum droplet impact and adherence efficiency and minimum inter-particle agglomeration in a Würster-style coating operation. This enabled the prediction of two key design parameters, the nozzle distance from the powder impact point and the Würster insert height. The span in design parameters showed that there is significant opportunity for design optimisation based on the critical X concept. A probe tack test was used to map the level of stickiness of droplets of different coating materials as they dried. As skin formation progressed, the stickiness passed through a maximum, in most cases to arrive at a point at which the droplet was no longer sticky at all (non-adhesive state). The maximum point of stickiness represents the ideal state to ensure successful droplet-substrate impact and adherence. The minimum point of stickiness represents the ideal state to prevent unwanted inter-particle agglomeration. The time interval between the onset of stickiness and the non-adhesive state was particularly dependent on the addition of plasticisers, but also on the formulation and the drying air conditions. Future work should look to establish a possible relationship between the surface glass transition temperature and the probe tack test stickiness measurements. The impact and spreading of droplets containing maltodextrin DE5 on to solid anhydrous milkfat was studied using a high speed video camera. It was found that the final spread diameter was able to be fixed close to the maximum spread diameter by using surfactants, thus avoiding significant recoil. Because existing literature focuses on predicting the maximum spread diameter, this work defines a need for adequate prediction methods for the final spread diameter, as this is the significant parameter in coating applications. Formulation and operating guidelines were established to independently optimise each micro-level process. These were used in a series of population based coating experiments in a pilot-scale Würster coater. This study highlighted the limited flexibility of the standard 'off-the-shelf' Würster coating apparatus for the coating of fine sized dairy powders. Because of this, the validation of the guidelines were inconclusive and optimisation could not be carried out. Further validation work is required on a custom-built apparatus for dairy powders. This work has advanced the fundamental knowledge of the coating process and is independent of material, equipment and scale. This knowledge, based on physical and chemical mechanisms, can be used to develop coating formulations and identify optimum process conditions for successful coating in less time and at less expense than is current practice. The next step is to put the guidelines into practice and craft the engineering of a continuous coating apparatus for dairy powder applications.
Keywords: Dairy powder coating; Spray drying; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290103 Food processing